Targeting T Cell Metabolism for Tumor Therapy: A Review - Cinthya Karlina Wijaya; Febriana Catur Iswanti (http://dharmais.co.id/, 2026)
Background: Immunometabolism explores the connection between metabolism and the immune system. T cells require nutrients like glucose, lipids, and amino acids for proper function, but tumors compete for these resources and create a suppressive microenvironment that weakens T cell activity. This article examines how T cell metabolism affects antitumor immunity and whether targeting metabolic pathways can improve cancer treatment. Methods: A narrative review was conducted by searching databases like PubMed, Scopus, and Google Scholar using keywords such as